Democracy at the point of bayonets - Peceny, Mark (Pennsylvania State University Press, 1999)
No country has worked harder to coerce others to adopt liberal institutions than the United States. This book examines the promotion of democracy during U.S. military interventions in the twentieth century, showing it to be one of the central ways in which the United States attempts to reconcile the potential contradictions involved in being a liberal great power. Examining interventions from the Spanish-American War through recent actions in Bosnia, Mark Peceny shows how the United States has encouraged the institution of free elections and other liberal reforms—often at the point of bayonets. Peceny applies statistical analysis to ninety-three cases of intervention and presents six case studies: Cuba and the Philippines after the Spanish-American War, Vietnam during the Kennedy administration, El Salvador during Reagan's first term, and Clinton's interventions in Haiti and Bosnia. By forging a synthesis of realist and domestic liberal approaches, Peceny illuminates the roles that both security concerns and liberal values play in the formulation and implementation of foreign policy. He shows how presidents often initially choose proliberalization policies to serve U.S. security interests and how Congress exerts pressure when presidents fail to take the initiative. Under these circumstances, he shows, presidents use the promotion of democracy to build domestic political consensus and to legitimize interventions. Although the United States has failed to promote democracy in most interventions, Peceny demonstrates that it has often had a profound and positive impact on the democratization of target states. His study offers new insight into the relationship between American power, the promotion of democracy, and prospects for the liberal peace in the decades to come.
Keywords: Intervention (International law) : History : 20th century; Military assistance, American : History : 20th century; National security : United States : History : 20th century; Democracy : History : 20th century; United States : Foreign relations : 20th century; United States : Military policy